APPLICATIONS COMPUTER SPARE PART SALES IN VISUAL BASIC STORES MSCOM DARI 6.0 - Ahmad Ihsan; Rahayu Noveandini, Skom, MM (Jurnal Sistem Informasi, 2006)
In scientific writing, the writer explains the data processing application programdesign spare computer parts store MSCOM especially on goods in cash sales andpurchases in cash by using Microsoft Visual Basic 6.0 and Visual Data Manager(VisData) to create a database.